The effects of subgrid-scale parameterizations in a zonally averaged ocean model - Knutti, Reto; Stocker, Thomas F.; Wright, Daniel G. (American Meteorological Society, 2000)
Isopycnal diffusion and an additional transport velocity parameterizing the effect of mesoscale eddies are implemented in the ocean component of a 2.5-dimensional zonally averaged coupled ocean–atmosphere model. The equilibrium states of the coupled ocean–atmosphere model, resulting from the different mixing parameterizations, are compared, and extensive parameter sensitivity studies are presented. For the equilibrium base states, the new mixing schemes result in changes in the distributions of temperature and salinity that are significant in the Southern Ocean, where the isopycnal surfaces are steep and the eddy-induced transport velocity approximately cancels the Deacon cell. The temperature and salinity changes are relatively small in the rest of the ocean. Furthermore, the implementation of the new mixing schemes results in significant changes in the strength and the pattern of the thermohaline circulation. Transient responses of the coupled ocean–atmosphere system in global warming scenarios are compared for the different mixing parameterizations. It is demonstrated that large changes in the stability of the thermohaline circulation occur and that the observed changes in stability are highly parameter dependent.